Performing Masculinities: Stereotypes and representations of the male body in contemporary South Africa - Manamela-Mogane, Owen (Department of Drama, 2019)
In this account of my practise as research into the crisis of masculinity among black males in South Africa, I am concerned with how men oppress and terrorize women and retard the recovery of South Africa from apartheid through crime, violence and transgressive actions. Following Sirkin (1984) in this paper I term this behaviour ‘hypermasculine’ and attribute it to the unfathomable violence inflicted on the black male body and psyche during apartheid while Danieli, (2007) and Goodman’s (2013) ‘transgenerational trauma’ accounts for why the condition persists. Butler’s idea of gender as a ‘performance’ theoretically grounds the hypermasculine body as a ‘mask’ behind which lies either a true and better male self or ‘shadow’– Seriti – or no self at all. Following this premise, I give an account of the creative process and performance of two PaR pieces (Seriti and Metsi) in which I unpack both the process and performances in which my own black male body was the medium for the research. I sketch my objectives of physically inhabiting the hypermasculine ‘performative’ stereotypes familiar to me from childhood township memories as well as in township theatre in order to define and ‘know’ them. Through exercises in weight, tempo and repetition I hoped to re-inscribe the misshapen figure of the black male. I discuss how working with an older black actor in Seriti yielded valuable insights into cultural male hierarchies, while the enactment of hypermasculinity took its toll necessitating mediation through traditional ritual. I recount how, with the need for healing now evoked in my body, and with an obsession in the shape of water, (Metsi) in the second research project I allowed the memory of the positive feminine presences in my past to inflect the male body with a different weight and shape in a disruption of the familiar and a glimpse of the potential of a new shape or self.